Pengaruh Media Ispringsuite9 Terhadap Hasil Belajar Peserta Didik Pada Pelajaran IPA Siswa Kelas V UPT SPF SD Negeri Labuang Baji 1 - Nuraeni Nuraeni; Nadrah Nadrah; Muh. Erwinto Imran (Journal Innovation In Education, 2023)
The purpose of this study was to determine the effect of ispringsuite9 media on science learning outcomes for fifth grade students of UPT SPF SD Negeri Laburan Baji 1. This type of research is quantitative or experimental (pre-experimental design) with a one-group pretest-posttest design. The sample and population were class V UPT SPF students at SD Negeri Labuang Baji 1, totaling 24 students. The instruments used to collect data are pretest, posttest and documentation. Data collection techniques in this study were observation and tests (pretest and posttest). The results showed that the data were analyzed using descriptive statistical analysis and inferential statistical analysis. Data were analyzed using descriptive statistical analysis. It was known that the mean pretest was 59.58 and was in the low category, namely 75%, while the posttest mean was 79.79, which was in the high category, namely 87.5%. the average value of the posttest is higher than the average value of the pretest and inferential statistical analysis using the t test formula, it is known that the t_count value obtained is 2.0686 with a frequency of df = 24-1 = 23, at a significance level = 0.05 obtained t_Table is 6.067. So t_(Count ) > t_Table or H_(0 ) is rejected H_1 is accepted. Based on the results of this study, it can be concluded that there is an influence of ispringsuite9 media on the science learning outcomes of class V UPT SPF SD Negeri Labunag Baji 1.